School size, student achievement, and the "power rating" of poverty: Substantive finding or statistical artifact? - Coladarci, Theodore (Education Policy Analysis Archives, 2006)
The proportion of variance in student achievement that is explained by student SES-"poverty's power rating," as some call it-tends to be lower among smaller schools than among larger schools. Smaller schools, many claim, are able to somehow disrupt the seemingly axiomatic association between SES and student achievement. Using eighth-grade data for 216 public schools in Maine, I explored the hypothesis that this in part is a statistical artifact of the greater volatility (lower reliability) of school-aggregated student achievement in smaller schools. This hypothesis received no support when reading achievement served as the dependent variable. In contrast, the hypothesis was supported when the dependent variable was mathematics achievement. For reasons considered in the discussion, however, I ultimately concluded that the latter results are insufficient to affirm the statistical-artifact hypothesis here as well. Implications for subsequent research are discussed.